Pengolahan Limbah Udang untuk Memperoleh Bahan Pakan Sumber Protein Hewani Pengganti Tepung Ikan - Mirzah Mirzah; Filawati Filawati (Universitas Andalas, 2013)
The objective of this study was to measure the effect of preparation the shrimp head waste to poultry feed. The experiment was conducted to examine the effect of soaking and steam heat treatment of shrimp heads waste (SHW) on nutrient and nutritional quality. The treatment is soaking and length of steam heat the shrimp heads waste. The experiment was designed in Completely Randomized Design, using factorial (3 x 3) with three replication. The first factors was three level concentration of the dusk rice solution (C1 = 10%; C2 = 20%; and C3 =30%), and the second factors was length steam heat ( W1 = 30 min; W2 = 45 min; and W3 = 60 min). Feed was soaked for 48 h prior to steam heat. The results showed that there was no interaction effects (P > 0.05) between concentration of the dusk rice solution and length of steam heat to dry matter (DM), crude protein (CP), lipid and fiber contents of SHW but length of steam factors was significant (P<0.05) to dry matter, crude protein, lipid and fiber contents of SHW and digestibility coefficient (in-vitro) of crude protein. There were interactions (P<0.01) concentration of the dusk rice solution and length of steam factors to chitin contents. There are no significant differences on metabolizable energy but nitrogen retention and protein digestibility was found to be significantly (P<0.05) between the SHW processed than unprocessed. Based on comparative cost analyses and nutritive value indicated, the best treatment was filtered of the dusk rice solution with concentratin 20 % and length of steam heat for 45 min.